Understanding rural and urban differences in the price and affordability of early childcare in the United States - Vincent H. Smith; Benjamin Goren (American Enterprise Institute (AEI), 2024)
Prices for, and the affordability of childcare has received increased attention since the advent of the COVID-19 pandemic. In addition, concerns have been raised about potential differences in childcare costs and access between rural and urban communities. To address these issues, we combine cross-sectional data from a 2018 survey of childcare prices in counties across eleven states with data on wages, rents, incomes, population and other demographic variables to estimate the determinants of county level prices for infant and pre-kindergarten childcare. Childcare prices for infants and pre-kindergarten four-year-old children are positively correlated with county level population, property rents, wage rates, median family incomes, and shares of adults with bachelor's degrees, which are substantially higher in more heavily populated urban counties. Thus, home and center-based care for infants and pre-kindergarten children is more expensive and, relative to household incomes, less affordable in urban counties than in rural counties.
Keywords: 330; Kinderbetreuung; Preis; Kosten; Ländlicher Raum; Stadt; Räumliche Verteilung; USA